Enhancing Vertical Jump Performance in Adolescent Female Volleyball Athletes: Effects of Squat Jumps and Knee Tuck Jumps for Health Promotion - Aprillia Setia Widiyawanti; Agung Wahyudi; Yovhandra Ockta (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
This experimental study examines the effectiveness of two plyometric training methods, squat jumps and knee tuck jumps, in enhancing vertical jump performance among U-12 female volleyball athletes. Vertical jump ability plays a critical role in executing offensive techniques such as spiking and defensive maneuvers like blocking. Fourteen athletes from the Dissporsa Kendal volleyball club participated in the study and were assigned to two experimental groups through ordinal pairing. Group A underwent squat jump training, while Group B received knee tuck jump training, each over the course of 16 sessions. A pre-test/post-test design was employed to assess changes in vertical jump performance. Descriptive statistics indicated improvements in both groups. Group A's average jump height increased from 27.83 cm to 31.50 cm (a 13.2% improvement), while Group B's average rose from 27.17 cm to 30.58 cm (a 12.7% improvement). The mean increase in jump height was 3.67 cm for Group A and 3.41 cm for Group B. However, an independent samples t-test revealed no statistically significant difference between the post-test results of the two groups (p = 0.8306), suggesting that both training methods were equally effective in improving vertical jump performance. These findings support the inclusion of squat jumps and knee tuck jumps in youth training programs aimed at developing lower-body explosive power. Due to their simplicity and accessibility, these exercises offer practical benefits for coaches and trainers working with young athletes. Future research involving larger sample sizes and extended training durations is recommended to further investigate the long-term effects of plyometric training on athletic performance and injury prevention in youth sports. Keywords: Plyometric, Vertical Jump, Volleyball, Youth Athletes, Training.